In Search of a “Social-AQI” - Ruchi Dwivedi; Muzamil Yaqoob; Aasim Khan; Praveen Priyadarshi; Saad Ahmad; Sudhir Attri; Raghava Mutharaju (South Asia Multidisciplinary Academic Journal)
Globally, datafication is being adopted as a solution for socio-environmental issues, with the belief that it will democratize decision-making by simplifying knowledge through data. However, this process can further alienate marginalized groups from governance by disregarding practical exposure levels and the sociopolitical contexts in which people live and engage at the community level. In this paper, we use community participation as a tool to develop the Social Air Quality Index (S-AQI), which shapes neighborhood air pollution mapping and monitoring in Delhi. We first question the impact of datafication on air pollution quality measurements and challenge the claim that air quality governance is possible simply through the deployment of high-tech devices and AQI standardization, which is often used to produce and share data about air pollution across Delhi. Instead, we propose an alternative community-oriented methodology and incorporate an interactive approach that relies on public workshops, offline questionnaires, and low-cost sensors to engage with six neighborhoods. Through this intervention-based approach, we seek to explore how to develop AQI understanding among local stakeholders and identify pathways to build greater social awareness and knowledge of AQI as a means of dealing with the pollution crisis.